Occurrence of dermoid cyst in the floor of the mouth: the importance of differential diagnosis in pediatric patients - Edela PURICELLI; Bernardo Ottoni Braga BARREIRO; Alexandre Silva QUEVEDO; Deise PONZONI
Abstract Lesions in the floor of the mouth can be a challenging diagnosis due to the variety of pathological conditions that might be found in this area. Within a broad range of lesions, attention has to be addressed to those that require specific management, such as a dermoid cyst (DC) and a ranula. Especially in pediatric patients, in whom the failure of diagnosis can postpone the correct treatment and cause sequelae later in life. DC, a developmental anomaly, is managed primarily by surgical resection. On the other hand, ranula is a pseudocyst that may be treated by marsupialization. This article reports a large and painful lesion in the floor of the mouth in a pediatric patient. With a diagnostic hypothesis of ranula, two surgical interventions were performed, but there were recurrences of the lesion. Subsequently, the patient was referred to the Oral and Maxillofacial Surgery Unit for re-evaluation. Computed tomography showed a semi-transparent image suggesting a cystic formation. Another surgical procedure was performed where the lesion was completely removed. Anatomopathological analysis confirmed the diagnosis of DC. The five-year follow-up showed no signs of recurrence. This article indicates that although DC in the floor of the mouth is rare, it should be considered in the differential diagnosis of other diseases in this area. This precaution may be particularly important in the following circumstances: 1) Similar lesions that have different therapeutic approaches and, 2) To prevent future sequelae in pediatric patients.